[Un]-Doing the Book «by the book:» Notes from the receiving end of Baz Luhrmann’s William Shakespeare’s Romeo + Juliet - Michel Modenessi, Alfredo (Poligrafías. Revista de Teoría Literaria y Literatura comparada, 2012)
Alfredo Michel Modonessi does an analysis about the William Shakespeare’s Romeo + Juliet by Baz Luhrmann, as an example of the historical depletion of Shakespeare’s book by inviting conversation on the interaction of «book» and cinema within the conditions of reception in our frame-and-screen-wise post-modern world. Practically no reviewer he have read, or any colleague with whom he have discussed it, have failed to label Luhrmann's film postmodern.